Development and evaluation of iManage: A self‐management app co‐designed by adolescents with sickle cell disease. Issue 1 (30th August 2016) - Crosby, Lori E.; Ware, Russell E.; Goldstein, Alana; Walton, Ashley; Joffe, Naomi E.; Vogel, Craig; Britto, Maria T.
Abstract: Background: Adolescents and young adults (AYAs) with sickle cell disease (SCD) are a vulnerable population with high risk of morbidity that could be decreased with effective self‐management. Previous research suggests that mobile applications (apps) may facilitate AYA engagement in health‐promoting behaviors. The objectives of this study were: (i) describe Internet access and use in AYA with SCD; (ii) identify barriers for self‐management in this population; (iii) collaborate with AYA to co‐design a mobile app that would minimize barriers; and (iv) evaluate the feasibility and acceptability of the app. Procedure: In phase 1, 46 AYAs with SCD 16–24 years of age completed a survey of Internet access and use. During phase 2, 19 AYAs with SCD (average age 20 ± 2.5 years) and eight healthcare providers participated in interviews to identify barriers and co‐design sessions to develop the app. In phase 3, five AYAs with SCD completed app feasibility and usability testing. Results: AYAs with SCD had daily Internet access (69%) using their computers (84%) or mobile phones (70%). Participants went online for health information (71%) and preferred Web sites with interactive/social features (83%). Barriers to self‐management included failing to believe that their health would suffer, lack of tailored self‐management support, lack of a mechanism to visualize self‐management progress, and limited opportunities for peer interaction around self‐management. The prototype app (iManage) was rated as highly feasible and beneficial. Conclusions: A mobile app prototype co‐designed by AYAs with SCD may be a useful tool for engaging them in self‐management strategies designed to improve health.